Serum antibody responses of juvenile and infant rhesus monkeys injected with Haemophilus influenzae type b and pneumococcus type 6A capsular polysaccharide-protein conjugates. - Schneerson, R (1984)
Juvenile and infant rhesus monkeys were injected subcutaneously with saline solutions of Haemophilus influenzae type b (Hib) and pneumococcus type 6A (Pn6A) capsular polysaccharides conjugated to either tetanus toxoid (TT), horseshoe crab hemocyanin, or cholera toxin (CT), and the antibody responses of the monkeys to both bacterial components were measured. All three Hib conjugates were immunogenic and elicited booster responses; their comparative immunogenicity was Hib-CT greater than Hib-TT greater than Hib-horseshoe crab hemocyanin. Hib alone did not elicit antibodies in the juveniles. Juveniles responded earlier and with higher levels of antibodies than did infants. TT, as well as diphtheria-tetanus toxoids-pertussis vaccine adsorbed injected concurrently at a separate site, increased both Hib and TT antibody responses in juveniles (P less than 0.05). Concurrent injection of 5 Lf of fluid TT with a nonimmunogenic 5-micrograms dose in infants elicited levels of Hib antibodies comparable to those elicited by 50 micrograms of Hib-TT. Hib antibodies elicited by the conjugates remained at protective levels in both juveniles and infants 2 months after the last injection, were bactericidal, and conferred passive immunity against bacteremia in infant rats. Passive immunization of juveniles with tetanus immune globulin before each injection of Hib-TT did not suppress Hib antibodies. Hib-TT and Hib-CT elicited increases of Hib antibodies of the immunoglobulin M and G isotypes in the infants. The Pn6A-TT conjugate was considerably less immunogenic than the Hib-TT conjugate; only a few of the juveniles or infants responded with protective levels of Pn6A antibodies. Pn6A antibodies from responders conferred protection in mice against intraperitoneal challenge with Pn6A organisms. TT antibodies were elicited in both juvenile and infant animals after one injection of 50 micrograms of Hib-TT and in the infants injected with 5 micrograms of Hib-TT plus 5 Lf of TT; 5 micrograms of Hib-TT and Pn6A-TT in combination alone did not elicit TT antibodies. Hib-CT elicited CT antibodies in both juveniles and infants.